Syntheses and crystal structures of 4-benzyl-1-ethyl-1,2,4-triazolium bromide and its corresponding NHC complexes of rhodium and iridium - Timothy G. Lerch; Daniel R. Albert; Michael Gau; Edward Rajaseelan (Acta Crystallographica Section E: Crystallographic Communications)
The syntheses and crystal structures of a triazolium salt, 4-benzyl-1-ethyl-1,2,4-triazolium bromide, C11H14N3+·Br− (2), and the corresponding N-heterocyclic carbene complexes, (4-benzyl-1-ethyl-1,2,4-triazol-5-ylidene)chlorido[(1,2,5,6-η)-cycloocta-1,5-diene]rhodium(I), [RhCl(C8H12)(C11H13N3)] (3), (4-benzyl-1-ethyl-1,2,4-triazol-5-ylidene)[(1,2,5,6-η)-cycloocta-1,5-diene](triphenylphosphane)iridium(I) tetrafluoridoborate, [Ir(C8H12)(C11H13N3)(C18H15P)]BF4 (5), and (4-benzyl-1-ethyl-1,2,4-triazol-5-ylidene)[(1,2,5,6-η)-cycloocta-1,5-diene](tricyclohexylphosphane)iridium(I) tetrafluoridoborate dicholoromethane sesquisolvate, [Ir(C8H12)(C11H13N3)(C18H33P)]BF4·1.5CH2Cl2 (6), are presented. Complexes 2 and 6 crystallize in the monoclinic space group P21/c, complex 3 in the triclinic space group P1 and complex 5 in the triclinic space group P1 with two molecules in the asymmetric unit. The three metal complexes 3, 5, and 6 have a distorted square-planar geometry around the metal ions. The N1—C1—N3 bond angle in the triazolium salt 2 is 107.1 (2)° and is observed in the range of 102.2 (3) to 103.8 (5)° in the NHC ligands in complexes 3, 5, and 6. The two substituent ‘wing tips' in the NHC ligand (N-ethyl and N-benzyl) are oriented in an anti-arrangement in compounds 2 and 3, a syn-arrangement in compound 6, and both syn and anti-arrangements in the two independent ion pairs in compound 5. All structures exhibit non-classical hydrogen-bonding interactions with the most acidic hydrogen atoms in complexes 2 and 3 playing critical roles in the orientations of structural units.